2020
DOI: 10.1002/ange.202012330
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐PROTACs: Degraders of RNA‐Binding Proteins

Abstract: Defects in the functions of RNA binding proteins (RBPs) are at the origin of many diseases; however, targeting RBPs with conventional drugs has proven difficult. PROTACs are a new class of drugs that mediate selective degradation of a target protein through a cell's ubiquitination machinery. PROTACs comprise a moiety that binds the selected protein, conjugated to a ligand of an E3 ligase. Herein, we introduce RNA‐PROTACs as a new concept in the targeting of RBPs. These chimeric structures employ small RNA mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 79 publications
0
17
0
1
Order By: Relevance
“…Of note, MTX-23 was orally bioavailable, causing a significant reduction in tumor growth at a dose of 8.3 mg/kg (Lee et al, 2020). Recently, a VHL-binding peptide was used to generate RNA-PROTACs that use oligonucleotides binding to specific RNA-binding proteins, such as LIN28 or RBFOX1, inducing their proteasomal degradation (Ghidini et al, 2021).…”
Section: Classes Of E3 Ligasesmentioning
confidence: 99%
“…Of note, MTX-23 was orally bioavailable, causing a significant reduction in tumor growth at a dose of 8.3 mg/kg (Lee et al, 2020). Recently, a VHL-binding peptide was used to generate RNA-PROTACs that use oligonucleotides binding to specific RNA-binding proteins, such as LIN28 or RBFOX1, inducing their proteasomal degradation (Ghidini et al, 2021).…”
Section: Classes Of E3 Ligasesmentioning
confidence: 99%
“…Alice Ghidini and colleagues developed a new technology named RNA‐PROTAC. As the name implies, this technology utilizes small RNA mimics as the warhead of RNA binding proteins (RBPs) and a peptide derived from HIF‐1α as the E3 recruiter to degrade the stem cell factor LIN28, a posttranscriptional regulator significantly involved in the therapeutic resistance and immune escape of tumorgenesis 346–348 . This proof‐of‐concept provides a new method for degrading and simultaneously inhibiting RBPs, which until now is considered “undruggable”.…”
Section: Emerging Solutionsmentioning
confidence: 99%
“…As the name implies, this technology utilizes small RNA mimics as the warhead of RNA binding proteins (RBPs) and a peptide derived from HIF-1α as the E3 recruiter to degrade the stem cell factor LIN28, a posttranscriptional regulator significantly involved in the therapeutic resistance and immune escape of tumorgenesis. [346][347][348] This proof-of-concept provides a new method for degrading and simultaneously inhibiting RBPs, which until now is considered "undruggable". While this approach has some imperfections, especially RNA oligonucleotides are unstable, and the secondary structure of RNA secondary is required for proper interaction with RBPs.…”
Section: Novel Protein Degradation Technologymentioning
confidence: 99%
“…However, RBPs are usually undruggable by conventional therapies as well as by traditional PROTACs. Recently, Ghidini et al 1 described a new type of PROTAC, termed RNA-PROTAC, that selectively degrades RBPs, thereby expanding the PROTAC strategy for disease treatment.…”
mentioning
confidence: 99%
“…10,11 However, the discovery of effective RBP-targeted drugs remains challenging due to RBP's structurally variable binding-pockets, the requirement for complicated drug-screening assays, and the presence of homologous domains recognizing short and degenerate sequence motifs. 9 In their recent study, Ghidini et al 1 reported a new type of PROTAC, termed RNA-PRO-TAC, that aims to degrade RBPs. Based on the established pre-let-7/Lin28 complex, 11 the authors utilized the key partial sequence (AGGAGAU) of pre-let-7 that binds to Lin28 as the POI ligand, together with a peptide ligand for E3 ligase von Hippel-Lindau (VHL) and a peptide linker to form the RNA-PROTAC ORN3P1 (Figure 1B).…”
mentioning
confidence: 99%